Evaluation of business intelligence projects success - a case study - Teixeira, Ana (2019)
Background: Many studies found in literature only focus on specific aspects of the evaluation of the success of projects, such as the criteria for evaluation; and just a few are focused on the activities for evaluating success. Objectives: The goal of the paper is to present the process for evaluating the success of Business Intelligence (BI) projects in a large company. Methods/Approach: An exploratory case study was carried out at Tintas Robbialac, SA, a Portuguese company of the paint industry. Results: The specific company approach for evaluating the success of BI projects is presented and discussed. Conclusions: The process for evaluating the success of BI, as well as the evaluation criteria, should be formally defined; and the success should be evaluated and monitored along all the project lifecycle.